2022
DOI: 10.3389/fpubh.2022.839967
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Does Not Affect Reproductive Health Parameters in Men

Abstract: With the implementation of COVID-19 vaccine up-take, doubts regarding the impact of immunization on future fertility have begun to emerge. We have examined vaccine safety on male reproductive health. We set up a multicentre (three infertility centers), retrospective study in order to assess semen parameters and fertilization rate of one hundred-six men in a pairwise comparison between the first and second assisted reproduction technology (ART) attempt, performed respectively before and after COVID-19 vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 27 publications
5
55
0
1
Order By: Relevance
“…Another study compared the changes in sperm parameters of 43 men before and after receiving the BNT162b2 mRNA Covid‐19 vaccine (Pfizer BioNTech), and found that there was no change in sperm parameters after vaccination (Safrai et al, 2022 ). Similar results were also reported by Reschini et al ( 2022 ). In a prospective cohort study conducted in Israel between February and March of 2021, semen samples from 75 fertile men were analysed 1–2 months following their second dose of Pfizer's COVID‐19 vaccine, and the sperm parameters were compared with the World Health Organization (WHO) reference ranges.…”
Section: Discussionsupporting
confidence: 92%
“…Another study compared the changes in sperm parameters of 43 men before and after receiving the BNT162b2 mRNA Covid‐19 vaccine (Pfizer BioNTech), and found that there was no change in sperm parameters after vaccination (Safrai et al, 2022 ). Similar results were also reported by Reschini et al ( 2022 ). In a prospective cohort study conducted in Israel between February and March of 2021, semen samples from 75 fertile men were analysed 1–2 months following their second dose of Pfizer's COVID‐19 vaccine, and the sperm parameters were compared with the World Health Organization (WHO) reference ranges.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies to date have found no association between mRNA COVID-19 vaccine and sperm parameters [9][10][11][12], follicular function [13][14][15][16][17] as well as embryo development [14,15]. With a specific focus on in vitro fertilization (IVF) cycles using preimplantation genetic testing for aneuploidy (PGT-A), one study further demonstrated similar euploidy rate after mRNA COVID-19 vaccination on adjusted analysis [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, semen parameters and fertilization rates were compared pre- and post-vaccination in patients undergoing ART. At a median follow-up of 75 days, no differences were noted between groups [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA SARS-CoV-2 vaccine, introduced in late 2020, dramatically reduced COVID-19 infection and transmission with consequent decrease in hospitalization and death rates within the general population [ 7 , 8 ]. Following the implementation of the mRNA SARS-CoV-2 vaccine, several studies were conducted to explore possible adverse outcomes of the vaccine on male fertility, confirming its safety on short-term follow-up [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation